Developmental Changes in Scots Pine Transcriptome during Heartwood Formation . Issue 3 (6th September 2016) - Lim, Kean-Jin; Paasela, Tanja; Harju, Anni; Venäläinen, Martti; Paulin, Lars; Auvinen, Petri; Kärkkäinen, Katri; Teeri, Teemu H.
Abstract : The Scots pine heartwood formation takes place in the summer and is marked by programmed cell death. Abstract: Scots pine ( Pinus sylvestris L.) wood is desired in woodworking industries due to its favorable timber characteristics and natural durability that is contributed by heartwood extractives. It has been discussed whether the Scots pine heartwood extractives (mainly stilbenes and resin acids) are synthesized in the cells of the transition zone between sapwood and heartwood, or if they are transported from the sapwood. Timing of heartwood formation during the yearly cycle has also not been unambiguously defined. We measured steady-state mRNA levels in Scots pine transition zone and sapwood using RNA sequencing. Year-round expression profiles of selected transcripts were further investigated by quantitative RT-PCR. Differentially accumulating transcripts suggest that, of the Scots pine heartwood extractives, stilbenes are synthesized in situ in the transition zone and gain their carbon-skeletons from Suc and triglycerides. Resin acids, on the other hand, are synthesized early in the spring mainly in the sapwood, meaning that they must be transported to the heartwood transition zone. Heartwood formation is marked by programmed cell death that occurs during the summer months in the transition zone.